Legalitas Usaha Bagi Eks Narapidana Terorisme (Eks Napiter) - Masyhar, Ali (Fakultas Hukum, Universitas Negeri Semarang, 2020)
One of the important factors in the efforts to deradicalise the ex prisoners of terrorists (ex-terrorists) is the acceptance of the community to return to a normal life in the midst of their community interactions. To live a normal life in the midst of society, decent work is also needed to support daily needs. In general, ex-terrorist - after undergoing their crimes - find it difficult / difficult to start a new life by working like a community. Jobs that are often their choice are home entrepreneurs / home industry and culinary businesses. In running this business, they often stumble over the legality of their business. Business legality is very important to provide the initial foundation for the establishment of the business concerned. For home-based entrepreneurs, a business license is needed, even a trademark for the products they produce. As for the culinary business, legality is required in relation to location leases, agreements with third parties and others.